Asas Kerahasiaan Bank dalam Penyidikan Tindak Pidana Penggelapan Dikaitkan dengan Undang-Undang Nomor 8 Tahun 1981 tentang KUHAP - Alifa Febiola Yasmin; Maman Budiman (ILIN Institute, 2024)
This research aims to analyze the implementation of the bank secrecy principle which becomes an obstacle for the police in investigating embezzlement crimes. The study used is juridical-normative method with a qualitative analysis. Techniques of data collection using Statute Approach and library research. The source of law used includes primer, sekunder, and ternary data. Primary sources by reviewing the legislation. Secondary data is taken from the literature in the field of law as well as expert opinions of scholars. Tertiary data through interview guidelines with investigators of the Criminal Investigation Unit at the Bandung City Police Resort. The results show that banking has a very strict confidentiality principle; police investigations experience obstacles related to the application of the principle of bank secrecy; and there is an imbalance between the Banking Law and the Criminal Procedure Code, causing confusion for banks and police investigators.